MLL-SEPT5 fusion transcript in infant acute myeloid leukemia with t(11;22)(q23;q11). Issue 3 (March 2014) - Launay, Erika; Henry, Catherine; Meyer, Claus; Chappé, Céline; Taque, Sophie; Boulland, Marie-Laure; Ben Abdelali, Raouf; Dugay, Frédéric; Marschalek, Rolf; Bastard, Christian; Fest, Thierry; Gandemer, Virginie; et al.
Abstract Chromosomal rearrangements involving the MLL gene at band 11q23 are the most common genetic alteration encountered in infant acute myeloid leukemia. Reciprocal translocation represents the most frequent form of MLL rearrangement. Currently, more than 60 partner genes have been identified. We report here a case of de novo acute myeloid leukemia with a t(11;22)(q23;q11) in a 23-month-old child. Fluorescence in situ hybridization study revealed that the 3'MLL segment was translocated onto the derivative chromosome 22 and the breakpoint on chromosome 22 was located in or near the SEPT5 gene at 22q11.21. Long distance inverse-polymerase chain reaction was used to identify precisely the MLL partner gene and confirmed the MLL–SEPT5 fusion transcript. Involvement of the SEPT5 gene in MLL rearrangement occurs very rarely. Clinical, cytogenetic and molecular features of acute myeloid leukemia with a MLL–SEPT5 fusion gene are reviewed.